2017
DOI: 10.1152/ajpheart.00509.2016
|View full text |Cite
|
Sign up to set email alerts
|

L5-LDL from ST-elevation myocardial infarction patients induces IL-1β production via LOX-1 and NLRP3 inflammasome activation in macrophages

Abstract: This study represents the evidence linking L5-LDL and the inflammatory cytokine IL-1β in ST-segment elevation myocardial infarction (STEMI). We elucidate the molecular mechanism underlying L5-LDL-induced production of IL-1β in macrophages. The results showed that L5-LDL induced activation of caspase-1 and NF-κB through the lectin-type oxidized LDL receptor (LOX-1)-dependent pathway, leading to the production of IL-1β.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 50 publications
2
33
0
2
Order By: Relevance
“…This occurred in the absence of changes in cell proliferation or mortality. According to our results, in THP1 macrophages, L5 from infarcted patients also induced IL1β release [17], and L5 from rabbits fed an atherogenic diet induced IL1β and IL6 [19]. The induction of IL10, a cytokine that suppresses macrophage activation and inflammation [35], could regulate an excessive inflammatory response to LDL(−), as was previously described in circulating monocytes [31].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This occurred in the absence of changes in cell proliferation or mortality. According to our results, in THP1 macrophages, L5 from infarcted patients also induced IL1β release [17], and L5 from rabbits fed an atherogenic diet induced IL1β and IL6 [19]. The induction of IL10, a cytokine that suppresses macrophage activation and inflammation [35], could regulate an excessive inflammatory response to LDL(−), as was previously described in circulating monocytes [31].…”
Section: Discussionsupporting
confidence: 80%
“…Their expression increases in differentiated macrophages vs. monocytes, as they are highly expressed in lipid-laden macrophages, and particularly in the presence of stimuli, such as OxLDL [42,43]. Previous studies have reported the involvement of these receptors in some LDL(−) actions in macrophages [16,17]. Taken together, these observations suggest the involvement of LOX-1 and CD36 in the LDL(−) effects described in the current study.…”
Section: Discussionsupporting
confidence: 78%
“…Modified LDLs play a key role in atherogenesis and atherosclerosis progression, and induce atherosclerotic lesions through complex inflammatory and immunological mechanisms [ 19 ]. In the vascular wall, modified lipoproteins act as toxic compounds, thereby promoting foam cell activation, macrophage proliferation and migration, as well as excessive matrix extracellular remodeling by increased metalloproteinase (MMP) production [ 46 , 47 , 48 , 49 ]. The presence of modified LDLs in the vascular wall, together with pro-inflammatory cytokines, high levels of nitric oxide, and mechanical injury, can lead to apoptosis of VSMCs, which produces fibrous cap thinning and necrotic core formation, with calcification of the atherosclerotic plaques [ 50 ].…”
Section: Lrp1 In the Metabolic Syndromementioning
confidence: 99%
“…The search did not include the use of antibodies for flow cytometry, ELISAs, or blocking studies. From the search results, we evaluated all articles published in 2017, for a total of 28 articles ( 2 , 8 11 , 13 , 15 , 16 , 19 , 21 , 22 , 26 28 , 30 , 32 , 34 , 41 , 42 , 44 , 45 , 47 , 48 , 50 52 , 54 , 58 ). Of these, 79% (22 of 28 articles) used immunoblot analysis, and 39% (11 of 28 articles) used immunohistochemistry (5 articles of the 28 evaluated used both techniques, 18%).…”
Section: Antibody Use In American Journal Of Physiology-heamentioning
confidence: 99%